Implication of Interleukin-17 in psoriatic lesion as Koebner phenomenon caused by recurrent occupational burns - Ayumi Sato; Takeshi Fukumoto; Ai Yoshioka; Chikako Nishigori (Dermatology Reports, 2022)
Koebner phenomenon (KP) is the emergence of new lesions in the uninvolved skin area caused by some sorts of stimulations including mechanical stress, chemical stress, trauma or injury. KP is frequently observed in patients with psoriasis and many triggers for developing KP have been reported. We report a case of a 43-year-old obese male welder developed psoriatic lesions only on areas of repeated burns due to occupation [...]